PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2020/2021 - Putu Mirayani; I Wayan Widana; Ni Kadek Rini Purwati (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
Critical thinking skills and learning models can affect learning outcomes. This study aims to determine the comparison of student learning outcomes with high and low critical thinking skills that adjust the application of problem-solving or conventional. The population in this study were students of class XI MIPA 1 and XI MIPA 8, and the research sample used a percentage of 27% below and above from the research population. The research instrument was a test of critical thinking skills and mathematics learning outcomes. The data obtained were analyzed using 2-way Anova analysis. The results of the study show that: (1) there is a comparison of the average learning outcomes between students who use problem-solving education models with conventional (mean 75.91 and 50.68), (2) there is an interaction between learning models and critical thinking skills on mathematics learning outcomes (Sig. 0.031 with = 0.05), (3) to students with high critical thinking skills, there is a comparison of learning outcomes between students who use problem-solving models with conventional (Qcount 7.80 with = 0.05), ( 4) for students with low critical thinking skills, there is a comparison of learning outcomes between students who use problem-solving education models and conventional ones (Qcount 3.16 with = 0.05).